2009
DOI: 10.1111/j.1478-3231.2009.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C virus infection associated with autonomic dysfunction

Abstract: Our results suggest that impaired autonomic function is caused by chronic HCV infection. Further studies are needed, however, to identify the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
26
0
3
Order By: Relevance
“…VM was abnormal in 58.3% of patients. Autonomic tests results are summarized in There is five other reports [3][4][5][6][7] focusing autonomic function in HCV-infected patients. They did not included cases with sensory polyneuropathy neither made large ACT tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VM was abnormal in 58.3% of patients. Autonomic tests results are summarized in There is five other reports [3][4][5][6][7] focusing autonomic function in HCV-infected patients. They did not included cases with sensory polyneuropathy neither made large ACT tests.…”
Section: Resultsmentioning
confidence: 99%
“…These authors detected dysfunction of the cardiac vagal system especially in patients with HIV and HCV coinfection, associated with depletion of glutathione. A multivariate analysis of 45 HCV-infected patients and 40 controls subjects showed that autonomic dysfunction in the former group was not associated with serum HCV RNA levels and cryoglobulins 7 . We can consider that HCV-infected patients with sensory polyneuropathy and complaint of dizziness support the needed of autonomic cardiovascular function investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, autonomic dysfunction is frequently seen in patients with various levels of liver disease [53], including early stages [54][55][56][57][58][59], and may manifest as frequent falls, blackouts, orthostatic hypotension, and syncope. It has also been linked to sudden cardiac death and mortality [53].…”
Section: Cardiac and Autonomic Abnormalitiesmentioning
confidence: 99%
“…Auch die Infektion mit dem Hepatitis-C-Virus kann mit Schädigungen des zentralen, peripheren und autonomen Nervensystems einhergehen [1,14,17,19,24]. Am besten etabliert ist die Verbindung der HCV-assoziierten Neuropathie mit der Kryoglobulinämie [14,17], in vielen Fällen ist die Pathogenese aber noch unklar.…”
Section: Abb 3 8 Nachweis Des Hepatitis-c-virus Imunclassified